CARDIOONCOLOGICAL AND TELEMEDICAL CARE IN PATIENTS WITH COLON CANCER - MANAGEMENT OPTIMISATION (CARTAGINA STUDY). (June 2018) - Styczkiewicz, K.; Medrek, S.; Styczkiewicz, M.; Jankowski, P.; Szmit, S.; Stec, S.
Abstract : Objective: Cardiovascular (CV) diseases and cancer constitute the main causes of contemporary death reasons. CV prevention in patients with colon cancer enable implementation of more effective, life-saving oncological treatment and might prevent distant CV mortality in cancer survivors. Unfortunately, available data shows that prevention actions are rarely undertaken in oncological patients compared to patients without cancer. The aim of the planned study is developing a model cardiooncological care programme, ON-CARDIO" in patients with colon cancer emphasizing the role of telemedicine and prevention. In particular the study is aiming at: The assessment if telemedical care programme, ON-CARDIO" implementation will result in obtaining the cardiooncological prevention goals Determining the type and demand on cardiooncological interventions using the, ON-CARDIO" programme The assessment of implemented cardiooncological interventions on control level of cardiovascular risk factors and frequency of cardiological complications in patients with colon cancer The assessment of heart rhythm disorders frequency and their relationship with oncological therapy using ECG telemonitoring with AliveCor Kardia Mobile application Assessing the influence of oncological therapy in colon cancer on blood pressure level, left ventricle function, cardiac arrhythmia and potential signs of ischemia Determining the influence of applied cardiooncological interventions on biochemistry parameters (NT-proBNP, troponin, CRP, HbA1c, lipid panel) Design and method: Figure. No caption available. Results: The programme is planned to be started this year, so far no results are available. The research hypothesis assumes that implementation of intensive, complex cardiooncological care using the model telemedical care programme, ON-CARDIO" will influence on achieving the cardiooncological prevention goals, contribute to early detection of cardiological complications occurring along with oncological therapy and will serve as a prototype for building similar systems in other cancer diseases. Conclusions: The above described project constitutes original, authorial idea, so far in medical literature there are no available data in this field. This programme for the first time will provide significant contribution and new knowledge concerning the role of telemedicine and cardiooncological prevention in patients with colon cancer characterized by similar risk profile as in CV diseases, which may subsequently lead to improvement of their prognosis.